The Importance of Management Control by Responsibility Centres in SMEs: A Successful Case Study - Romana, Fernando Acabado; Gestoso, Carlos Guillen; Fernandez, Silvia Gonzalez; Santos, António Morais (Archives of Business Research, 2023)
This work was initially carried out with a survey on the importance of responsibility centers in small and medium-sized enterprises (SMEs). After some research I came across the fact that the literature is very focused on large companies, and not so much on SMEs. This fact is not directly proportional to reality, since 99.9% of companies are SMEs and only 0.01% are large companies. Having the possibility of obtaining an investigation in a specific case of an SME that did not use the management control by centers of responsibility, it was proposed to the administration to change the working methods, so that the analyzes were more real. For this, it was necessary to make a work planning, where all the area directors were involved, in order to obtain the results in a short space of time, it was also necessary to involve the Enterprise Resource Planning (ERP) partner, so that the system had properly programmed, with the new needs of the company.